Alterations of gray and white matter morphology in obsessive compulsive disorder | Las alteraciones de morfologia de la sustancia blanca y gris en el trastorno obsesivo compulsivo - Gonçalves, Oscar F. (2017)
Background: While the ethio-pathogenesis of Obsessive-Compulsive disorder (OCD) remains unknown, there is increased evidence of widespread structural alterations in both white and gray matter in OCD patients that include, but are not restricted, to abnormalities in corticostriatal-thalamo-cortical (CSTC) regions. The objective of this study was to test the existence of structural alterations in both white and gray matter in a sample of OCD patients when compared with a group of non-clinical matched controls (NCC), using voxel-based morphometry (VBM). Method: Fifteen patients with OCD and 15 NCC underwent MRI structural scanning. Results: Frontal (increased gray matter in the middle frontal gyrus) and subcortical regions (increased white matter in the pallidum) were found to be affected in patients. Additionally, temporalparietal regions were also found to be affected and highly correlated with OCD symptom severity (decrease of gray matter in the superior parietal lobe and white matter in the angular and superior temporal gyri). Conclusions: These alterations may be associated with prominent OCD symptoms, such as diffi culties with inhibitory control (pallidum, angular gyrus), executive functioning (middle frontal gyris), compulsive checking (superior temporal gyrus) and visual-spatial defi cits (superior parietal lobe).